An efficiency analysis of cattle backgrounding operations in Kansas - L. Gow; Michael R. Langemeier (Kansas Agricultural Experiment Station Research Reports, 1999)
As the structure of the beef industry changes, understanding its efficiency, cost, and profitability relationships is important. This study evaluates the relative efficiency of a sample of Kansas farm backgrounding and backgrounding/finishing operations for 1995- 1997. No commercial feeders were included. On average, backgrounding operations were 71% technically efficient, 68% allocatively efficient, 83% scale efficient, and 39% overall efficient. The results suggest that Kansas backgrounding operations could reduce their cost by 61%, if all farms were producing at the lowest possible cost. On average, backgrounding/finishing operations were 84% technically efficient, 79% allocatively efficient, 90% scale efficient, and 60% overall efficient, suggesting that those operations could reduce their cost by 40%, if all were producing at the lowest possible cost. Given the average levels of technical, allocative, and overall efficiencies, significant room for improvement exists in technology adoption, input usage, and size adjustment for both backgrounding and backgrounding/finishing operations.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Backgrounding; Finishing; Production costs; Efficiency; Size